METHODS IN TRANSLATING PROVERBS IN MANGALA PAKPAHAN’S BOOK: BATAK TOBA KARAKTER KEARIFAN INDONESIA - SOLINA SIHOMBING; I WAYAN DIRGEYASA; MORADA TETTY (State University of Medan, 2021)
This study aimed to find out the method used in translating Batak Toba Proverbs into English and explain the reasons for the translation method used in Mangala Pakpahan’s book: Batak Toba character kearifan Indonesia. The research was conducted by using the descriptive qualitative method. The data were taken from Mangala Pakpahan’s book that contained 72 proverbs from the Batak Toba language. The findings of the study showed that not all methods were used in translating the proverbs. They were the adaptation translation method (69.44%), followed by the communicative translation method (12.5%), free translation method (11.12%), and the last was the exact translation method (6.94%). Moreover, the reason for using the translation method in translating the proverbs was the translation sounds natural even though in the form of proverbs and is still focused on English grammatical rules. Translation method was also the easier way to be understood by the reader, and it keeps retaining the translation of the proverbs without altering the original meaning.